INTERACTIVE EFFECTS OF "TYPE A" BEHAVIOR AND PERCEIVED CONTROL ON WORKER PERFORMANCE, JOB SATISFACTION, AND SOMATIC COMPLAINTS. - Lee, C.; Ashford, S. J.; Bobko, P. (Academy of Management Journal, 1990)
This research examined the moderating role of perceived control on the relations between Type A behavior and worker performance, job satisfaction, and somatic complaints. Results suggest that peopl...